ANALISIS RASIO PROFITABILITAS DAN RASIO LIKUIDITAS DALAM MENILAI KINERJA KEUANGAN PADA PT ELECTRONIC CITY, Tbk - Yulia Wida Kristiani Gea; Rudy; Kadek Ayu Susiani Dewi; Nuraida (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2023)
The purpose of this study is to find out the performance finance Footwear companies listed on the Indonesia stock exchange for the periods 2012-2016 through analysis of cash flow statements. Method uses in this study is quantitative descriptive method. The data analysis technique uses is analysis of cash flow statements. As for the analysis of the cash flows statements uses is the ratio operating cash flows to current liability, the ratio of operating cash flow to interest, the ratio of operating cash flows to capital expenditures, the ratio of operating cash flows to total debt, the ratio of operating cash flows to net income. Based on the results of the study it can be concluded that the effectiveness of the financial performance of Footwear Companies listed on the Indonesia stock exchange during the period of 5 years (2012-2016) is not good, seen from the results of the calculation of the cash flow ratio operating cash flows to current liability and the ratio of operating cash flows to total debt under 1, describes that PT Primarindo Asia Infrastruktur, Tbk. and PT Sepatu Bata, Tbk.is unable to meet its obligation and its commitments, and some ratio during thin research (2012-2016) also shows a negative value.